Development of Residential Space for the ToKaili Community with a Phenomenological Approach in Central Sulawesi, Indonesia - Siradjuddin, Zaenal; Timbang, Gator; Suyuti, Lutfi (Applied Engineering and Technology, 2022)
The uniqueness of the evolutionary process of housing and housing provision is directed by developments in culture, technology, and knowledge. This study aims to reveal what is behind the phenomenon of providing houses from time to time. This study uses a qualitative method with a phenomenological approach. The results of this analysis found several periods of Settlement, ranging from nomadic to ideal permanent solutions and farming settlement hierarchies.